Integrated weed management in sunflower under modified spacing: INTEGRATED WEED MANAGEMENT IN SUNFLOWER UNDER MODIFIED SPACING - A MAHAPATRA; B B BISOYI; K RAMESH (Journal of Oilseeds Research, 2025)
A field experiment was conducted during summer, 2022 at OUAT, Bhubaneswar to quantify the effect of integrated weed management on sunflower. The objective was to evaluate the effect of modified spacing to facilitate mechanical weeding under modified spacing (75 cm x 25 cm) for the hybrid DRSH-1. Among the treatments tested, Pendimethalin @ 1 kg a.i/ha as pre-emergence fb Quizalofop-p-ethyl @ 37.5 g a.i/ha at 20 DAS was statistically on par with two intercultivations at 20 and 40 DAS fb one intercultivation at 20 DAS fb one hand weeding at 30 DAS. However, weed free (three hand weedings at 15, 30 and 45 DAS) recorded highest seed yield (2060 kg/ha) and oil yield (815 kg/ha) with highest net return (`55131/ha). Inclusion of a herbicide, Pendimethalin @ 1 kg a.i/ha as pre-emergence fb Quizalofop-p-ethyl @ 37.5 g a.i/ha at 20 DAS recorded the highest B:C ratio (1.88). It could be concluded that Pendimethalin @ 1 kg a.i/ha as pre-emergence fb Quizalofop-p-ethyl @ 37.5 g a.i/ha at 20 DAS is as effective as manual weeding.